2003
DOI: 10.1172/jci16913
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for proteinase-activated receptor-2 in arthritis

Abstract: Using physiological, pharmacological, and gene disruption approaches, we demonstrate that proteinase-activated receptor-2 (PAR-2) plays a pivotal role in mediating chronic inflammation. Using an adjuvant monoarthritis model of chronic inflammation, joint swelling was substantially inhibited in PAR-2-deficient mice, being reduced by more than fourfold compared with wild-type mice, with virtually no histological evidence of joint damage. Mice heterozygous for PAR-2 gene disruption showed an intermediate phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
217
3
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(233 citation statements)
references
References 20 publications
11
217
3
1
Order By: Relevance
“…43,44 In Par2 Ϫ/Ϫ , 46 -48 the birth rate lower than the Mendelial rate was noted in one report, 46 whereas the normal birth rate was observed in the other study. 47 Otherwise, Par2 Ϫ/Ϫ developed normally to adulthood. Par3 Ϫ/Ϫ 4 and Par4 Ϫ/Ϫ 49 were not embryonically lethal and the mice developed normally to adulthood.…”
Section: Par1mentioning
confidence: 98%
“…43,44 In Par2 Ϫ/Ϫ , 46 -48 the birth rate lower than the Mendelial rate was noted in one report, 46 whereas the normal birth rate was observed in the other study. 47 Otherwise, Par2 Ϫ/Ϫ developed normally to adulthood. Par3 Ϫ/Ϫ 4 and Par4 Ϫ/Ϫ 49 were not embryonically lethal and the mice developed normally to adulthood.…”
Section: Par1mentioning
confidence: 98%
“…In support of this role for PAR 2 , deletion of PAR 2 also protects against colitis induced by Citrobacter rodentium, allergic inflammation of the airways, and arthritis. [33][34][35][36] In contrast, pretreatment with PAR 2 -AP protects against chemically induced colitis due to the release of calcitonin gene-related peptide. 11 Although deletion of PAR 2 significantly diminished MPO, TxA-induced pathologic changes were more completely blocked.…”
Section: Contribution Of Par 2 To C Difficile Txa-induced Enteritismentioning
confidence: 99%
“…Synovial fibroblasts, chondrocytes, macrophages, neutrophils, mast cells, T cells, and dendritic cells all express PARs, which exhibit both antiinflammatory and proinflammatory properties, although recent data point toward a detrimental role especially in the context of immune-mediated effects in arthritis (157). A study in PAR-2 Ϫ/Ϫ mice confirmed PAR-2 as a key mediator of chronic joint inflammation (158), and this is likely to be a consequence of activation by mast cell-derived tryptase (86,87). PAR-2 is associated with the perpetuation of inflammation in both RA and OA, because PAR-2 levels are elevated by proinflammatory cytokines and growth factors (159,160), while PAR-2 activation in peripheral blood monocytes and chondrocytes enhances proinflammatory cytokine production (161,162).…”
Section: Serine Proteinases and Cell Signalingmentioning
confidence: 99%